Assessing changes in vascular permeability in a hamster model of viral hemorrhagic fever - Gowen, Brian B; Julander, Justin G; London, Nyall R; Wong, Min-Hui; Larson, Deanna; Morrey, John D; Li, Dean Y; Bray, Mike (Virology journal, 2010)
A number of RNA viruses cause viral hemorrhagic fever (VHF), in which proinflammatory mediators released from infected cells induce increased permeability of the endothelial lining of blood vessels, leading to loss of plasma volume, hypotension, multi-organ failure, shock and death. The optimal treatment of VHF should therefore include both the use of antiviral drugs to inhibit viral replication and measures to prevent or correct changes in vascular function. Although rodent models have been used to evaluate treatments for increased vascular permeability (VP) in bacterial sepsis, such studies have not been performed for VHF. Here, we use an established model of Pichinde virus infection of hamsters to demonstrate how changes in VP can be detected by intravenous infusion of Evans blue dye (EBD), and compare those measurements to changes in hematocrit, serum albumin concentration and serum levels of proinflammatory mediators. We show that EBD injected into sick animals in the late stage of infection is rapidly sequestered in the viscera, while in healthy animals it remains within the plasma, causing the skin to turn a marked blue color. This test could be used in live animals to detect increased VP and to assess the ability of antiviral drugs and vasoactive compounds to prevent its onset. Finally, we describe a multiplexed assay to measure levels of serum factors during the course of Pichinde arenavirus infection and demonstrate that viremia and subsequent increase in white blood cell counts precede the elaboration of inflammatory mediators, which is followed by increased VP and death. This level of model characterization is essential to the evaluation of novel interventions designed to control the effects of virus-induced hypercytokinemia on host vascular function in VHF, which could lead to improved survival.